Nankai Forearc Structural and Seismogenic Segmentation Caused by a Magmatic Intrusion off the Kii Peninsula. (19th August 2022) - Kimura, G.; Nakamura, Y.; Shiraishi, K.; Fujie, G.; Kodaira, S.; Tsuji, T.; Fukuchi, R.; Yamaguchi, A.
Abstract: The causes for forearc basin and megathrust rupture zone segmentation are controversial. The Nankai forearc, Japan, is separated into five domains based on topography: Enshu, Kumano, Muroto, Tosa, and Hyuga. The boundaries of these domains correspond to the rupture limits of large earthquakes. We examined the geologic structure of the boundary region between the Kumano and Muroto domains off the Kii Peninsula using multichannel seismic reflection data to evaluate the role of upper plate composition in controlling segmentation. The results suggest that thick cover sediments and underlying accretionary prism are obliquely thrust landward over the igneous basement complex rock in the region of offshore of Cape Shionomisaki and separate the forearc basin. The igneous basement complex rocks directly overlying the plate interface in the hypocentral regions of 1944 Tonankai and 1946 Nankai earthquakes. The 1944 earthquake originated at the base of the complex, and the rupture extent slipped past its basement boundary, whereas the 1946 event nucleated at the updip boundary of the basement complex. The dense igneous rocks might have worked as a heavily loaded barrier on the seismogenic megathrust and separated the rupture area of both the earthquakes. Upper plate geology may be an important factor in controlling seismogenesis in the Nankai Trough and may serve as an example for understanding the controls on megathrust slip in other subduction zones. Plain Language Summary: The Nankai Trough, Japan is the place where quakes nucleate in the margin and tsunamis repeatedly devastated circum‐Pacific societies. When, where, why, and how the quakes were started in the trench is a central scientific question but unsolved. The historical records of earthquakes suggest that the rupture started around Cape Shionomisaki of the Kii Peninsula, where there is also a topographic segment boundary of the ∼2, 000 m deep basin in the middle continental slope. Our research of the geologic structure beneath the earthquake epicenters indicates a dense and hard rock mass situated upon the hypocenters of 1944, and 1946 megaquakes off Cape Shionomisaki. The rock mass might have worked as a heavy load and barrier on the low angle dipping plate boundary fault when the fault slipped the large rupture was propagated in the Nankai Trough. Key Points: The Nankai forearc basin is separated off the Kii Peninsula owing to the existence of middle Miocene igneous basement in the upper plate The rupture areas of the 1944 Tonankai, 1946 Nankai, and 2016 off‐Mie earthquakes appear to be controlled by the igneous basement The shallow distribution of very low‐frequency earthquakes and tremors are related to the geological heterogeneity of the upper plate